THE PREVALENCE OF URINARY TRACT INFECTIONS AND THE AGENTS RESPONSIBLE FOR THEM IN PREGNANT WOMEN IN THE PROVINCE OF KARBALA - Al-baiaty, Shahad Kadhem Jafar; Ali, Sarah Akar; Al-Sarray, Riyam Ghazi Kareem; Mahdi, Hawra Raad; Jassab, Jinan Talib; Hussein, Basim Jawad (PT. Antis International Publisher, 2024)
Along with anemia and hypertension, urinary tract infections (UTIs) are among the most frequent medical problems of pregnancy, occurring in between 5% and 10% of pregnancies. This study set out to ascertain the frequency of urinary tract infections (UTIs) and the presence of uropathogens in expectant mothers. 417 urine samples were examined between December 2021 and August 2022 of that research period. When a urinary tract pathogen grew to at least 10 5 CFU/ml in a culture of a midstream urine sample, the diagnosis of UTI was made. Biochemical assays were used to identify the isolated microorganisms. According to the results, 49.4% of expectant mothers had a UTI. The most often isolated organism was E. Coli (56.79%), which was followed by Proteus sp (5.8%), Pseudomonas sp (6.3%), and Klebsiella sp (19.9%)..